Antimicrobial effect of green synthesized TiO2 nanoparticles against Cercospora canesces growth in mung bean - Afzal, Araba; Khan, M Asaf; Tahir, M Hammad Nadeem; Khan, Zulqurnain; Hassan, Zeeshan; Gechev , Tsanko; Ali, Zareena; Faisal, Dr. Muhammad (Journal of Agriculture and Biology, 2024)
Mung bean is one of the economically important leguminous crops generally grown in arid region of Pakistan. Mung bean grows best at 30-35℃ and is a nutrient enriched crop with higher amounts of starch (50%), proteins (18-25%), fat (3%) and fiber (3-4.5%). Many biotic factors affect crop production. Yield losses due to biotic factors are up to 40-80% in mung bean. Cercospora leaf spot (CLS) is very common disease in mung bean caused by hemi-biotrophic fungal pathogen Cercospora canescens. For sustainable agrocontrol there is need to develop alternative solutions for conventional methods. Green synthesized nanoparticles offer promising solution to mitigate adverse effect of agrochemicals and fungicides. In this review green synthesized TiO2 nanoparticles used to mitigate the disease severity by seed priming with 50mgL-1 and 150mgL-1 nanoparticles (NPs) suspension solution in mung bean. The result shows that 50mgL-1 Tio2-NPs inhibit fungal growth by 87.85% in in vitro and 74.07% in in vivo experiment. Tio2-NPs application improve root, shoot, leaf surface area, chlorophyll content, stomatal conductance and boost plant immunity by enhancing expression of the Pathogenesis-related (PR-1) gene in response stress. Therefore, present study indicates that green synthesized Tio2-NPs is an effective way to enhance the growth and productivity of mung bean by inhibiting C. canescens.
Keywords: Mung bean; Cercospora leaf spot; hemi-biotrophic; Cercospora canescens; nanoparticles; Pathogenesis-related (PR-1) gene